2008
DOI: 10.1007/s11605-007-0382-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical Quality of Life, Time, and Gender on Change in Symptoms of Anxiety and Depression after Liver Transplantation

Abstract: Previous research demonstrated that physical health-related quality of life (HRQOL) improves after liver transplantation, but improvements in mental HRQOL are less dramatic. The aim of this study was to test the effects of physical HRQOL, time post-transplant, and gender on pre- to post-transplant change in anxiety and depression. Longitudinal HRQOL data were prospectively collected at specific times before and after liver transplantation using the SF-36(R) Health Survey (SF-36), Center for Epidemiologic Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 12 publications
2
45
3
Order By: Relevance
“…[48] Moreover, liver transplant recipients are at increased risk of stress due to pre-existing liver failure, functional impairment of graft, rejections and immunosuppression. [49] Based on these findings, it is important for clients to develop strategies to deal with their emotions and to manage stress.…”
Section: Discussionmentioning
confidence: 99%
“…[48] Moreover, liver transplant recipients are at increased risk of stress due to pre-existing liver failure, functional impairment of graft, rejections and immunosuppression. [49] Based on these findings, it is important for clients to develop strategies to deal with their emotions and to manage stress.…”
Section: Discussionmentioning
confidence: 99%
“…They tested differences in the following domains: liver disease symptoms, concentration, memory, worrying about the disease and sexual problems. Russell et al 2008, with the administration of, SF-36 the Center for Epidemiologic Studies Depression Scale (CES-D), and Beck Anxiety Inventory Scale, observed similar results.…”
Section: Cognitive Operations Preference Enquiry-easy (Cope-easy) (Frmentioning
confidence: 55%
“…Studies show that fighting spirit and denial are ways of coping better than the rest, in the sense that facilitate adjustment to illness (Carver, 2005;Russell, 2008).…”
Section: The Importance Of Psychological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…37,41 Others have suggested a positive correlation between physical and mental health-related quality of life in posttransplant patients. 42 …”
Section: Anxietymentioning
confidence: 99%